Unmet need in fertile age couples based on PK-21 data at stunting locus in Tapin Regency - Palimbo, Adriana; Marlena, Leny; Redjeki, Dwi Sogi Sri; Tambun, M S M O Siska Selvija (Health Sciences International Journal, 2025)
Background: Unmet need for family planning remains a significant public health issue, particularly in regions with high population growth and stunting prevalence. Tapin Regency in South Kalimantan Province experiences challenges in achieving family planning targets, with unmet need contributing to elevated fertility rates and population growth. Objective:  This study aims to analyze the unmet need for family planning among fertile age couples in stunting locus sub-districts of Tapin Regency, focusing on the distribution of unmet need for spacing and limiting, and identifying potential areas for targeted intervention. Method:  A descriptive survey design was employed using secondary data from the PK-21 (Pendataan Keluarga 2021 [En: Family Cencus – 2021]) database provided by the National Population and Family Planning Board (BKKBN). The study analyzed data from 12 sub-districts identified as stunting loci in Tapin Regency. The data included total unmet need, unmet need for spacing, and unmet need for limiting, which were quantitatively processed and presented as percentages. Results:  The analysis revealed that the total unmet need in Tapin Regency reached 9.5%. The unmet need for limiting (65.1%) was significantly higher than for spacing (34.8%). Among the sub-districts, Binuang recorded the highest total unmet need (19.2%), while South Candi Laras had the lowest (3.5%). Sub-districts with higher unmet need were found to have greater challenges in family planning program implementation, necessitating targeted interventions. Conclusion: Unmet need for limiting dominates the family planning challenges in Tapin Regency, particularly in sub-districts with high fertility rates. Addressing these unmet needs requires tailored strategies, including enhancing awareness, accessibility, and cultural sensitivity of family planning programs.